Synthesis and Characterization of SnS: 3%Bi thin Films for Photovoltaic Applications - Al-Maiyaly, Bushra K.H.; Duaa Muneer Sadiq (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In the present article, Nano crystalline SnS and SnS:3% Bi thin films were fabricated using thermal evaporation with 400±20 nm thickness at room temperature at a rate deposition rate of 0.5 ±0.01nm /sec then annealing for one hour at 573 K for photovoltaic application. The prepared samples were characterized in order to investigate the structural, electrical, morphological, and optical properties using diverse techniques. XRD and SEM were recorded to investigate the effect of doping and annealing on structural and morphological possessions, respectively. XRD showed an SnS phase with polycrystalline and appeared to form an orthorhombic structure, with the distinguish trend along the (111) grade, varying crystallite size from (19.45-25.95) nm after doping and annealing. SEM investigations of these films show extremely fine nanostructures and demonstrated excellent adhesion, after Bi-doping, the nanostructures remained identical with a little change. UV/Visible studies were made in the range of wavelength (300-1100) nm to calculate the optical constants for these films. These measurements revealed a high value of the absorption coefficient and decrease the optical energy gap values from (1.85 -1.6) eV after doping with 3% Bi. The characterization of these films it can be chosen in the application of solar cells. On the other hand, the optical properties of SnS films have been enhanced by Bi-doping.